Detection of Congenital Mullerian Anomalies by Real-time 3D Sonography - Ahmadi, Firoozeh; Haghighi, Hadieh (Journal of Reproduction & Infertility, 2012)
Mullerian duct anomalies (MDAs) are relatively common disorders that are particularly responsible for obstetrical complications and have a prevalence of about 3%-4% in the general population (1, 2). Uterine malformations may result from arrested development of the mullerian ducts, failure of fusion of the mullerian ducts or failure of resorption of the median septum (1, 2).